The Integration of Corporate Governance and Risk Management Principles Is Reflected in the Quality of the External Auditor's Performance: Integrasi Prinsip Tata Kelola Perusahaan dan Manajemen Risiko Tercermin dari Kualitas Kinerja Auditor Eksternal - Hashmi , Saddam Catea (Indonesian Journal of Law and Economics Review, 2024)
This research aims to explore governance and risk management's role in enhancing transparency, accountability, and the quality of external audit performance. It examines the responsibilities of external auditing in successful risk management and fostering trust among stakeholders. The study highlights the importance of compliance with international auditing standards, particularly ISA-265, in reporting deficiencies in internal control to governance and management. Using SPSS v26 and AMOS v26 for analysis, data were gathered from 255 auditors and accountants working in governance, risk management, and auditing within major Iraqi banks. Key topics include corporate governance, audit quality, the definition and significance of governance, and risk management’s methodology. Findings reveal a strong positive relationship between integrating corporate governance, risk management principles, and audit quality. Advanced governance practices and effective risk management create an environment that strengthens auditor independence and ensures accurate, objective audits. The research underscores the vital role of internal controls in governance and risk management, reducing fraud, detecting manipulation early, and achieving audit quality. These insights guide organizations in fostering transparency, meeting goals, and bolstering confidence among investors and stakeholders. Highlights: Governance and risk management enhance transparency and audit quality. External auditing supports risk management, independence, and fraud detection. Compliance with standards ensures effective audits and investor confidence. Keywords: governance, risk management, audit quality